Desenvolvimento e validação de método analítico, avaliação da atividade antioxidante, antitumoral e toxicidade de um fotoprotetor obtido a partir de extrato de folhas de Arrabidaea chica - Siraichi, Jackeline Tiemy Guinoza (2013)
This work developed and validated an analytical method by HPLC to identification and quantification the flavonoids present in the plant, evaluated the antioxidant and antitumor activities of the extract and toxicity of a photoprotector formulation obtained from leaf extract of Arrabidaea chica. The analytical method developed by HPLC detected and quantified the presence of two majority flavonoids, scutellarein and apigenin. The method was validated and found to be linear, precise and accurate. The analysis of the antioxidant activity was done by the method of scavenging free radicals (DPPH-2,2-diphenyl-1-picrylhydrazyl), beta-carotene/ linoleic acid system and total reactive antioxidant parameters (TRAP). The extract obtained from leaves of A. chica showed significant antioxidant activity. TRAP method was used to compare the antioxidant activity of the crude extract with compounds (scutellarein and apigenin) isolated from the plant. The extract showed higher activity when compared to the two compounds separately. The antitumor activity was evaluated through the tests of cell viability and proliferation, genotoxicity testing and measurement of oxidative stress parameters using the crude extract (50- 400μg/mL) in murine melanoma cells B16F10. The extract showed cytotoxic effects and induction of DNA damage associated with a reduction in antioxidant defenses and increased levels of malondialdehyde (MDA), without the involvement of nitric oxide. The toxicity of photoprotective formulation was evaluated by applying the product on the left ear of rabbits in treated group and in the right ear, only distilled water, for 90 days. The control group was administered distilled water in both ears. Experiments were performed to evaluate macroscopic, microscopic, biochemical and hematological effects. Daily macroscopic observation indicated the presence of mild comedones and erythema in both groups. Microscopic analysis confirmed the presence of slight comedogenicity in the treated ear and preservation of the kidney, liver and spleen structures when compared to the control group. The biochemical and hematological parameters indicated the absence of renal and liver disorders. The photoprotective formulation tested showed no toxic effects in animals chronically treated. The extract of A. chica was standardized and showed significant antitumor and antioxidant activity, which may be a product with great possibility of incorporating in the pharmaceutical and cosmetic industry.